One Day Hands-On Workshop on Design of Experiment (DOE) using Design Expert - Noratikah, Abu (2023)
The Centre for Mathematical Sciences has successfully organised a One Day Hands-On Workshop on Design of Experiment (DOE) using Design Expert for the staff and researcher of Malaysian Agricultural Research and Development Institute (MARDI) Serdang, Selangor on 16 January 2023. The workshop was delivered by Dr. Noratikah Abu and Dr. Wan Nur Syahidah Wan Yusoff.